Degradasi Tradisi : Pernikahan Jawa Pada Masa Pandemi Covid-19 - Harsono Harsono; Adi Deswijaya; Pradnya Paramita Hapsari; Agus Efendi (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This study aims to explain the form of modification and the factors behind the degradation of traditional values in Javanese wedding ceremonies as a result of the implementation of PPKM during the Covid 19 pandemic. The data source in this study is the event of Javanese wedding traditions in Jatipuro Karanganyar. The data are in the form of behavior, actions, words, and symbols in the Javanese wedding event in Jatipuro Karanganyar. Collecting data using the listen method using the recording technique, and the advanced note-taking technique. The research uses qualitative methods with a phenomenological approach. The method of presenting the results of data analysis using informal methods. The results explain that restrictions on community activities during the pandemic have an impact on the modification of traditional wedding ceremonies. Javanese wedding traditions are sacred and noble and become a medium for the community in synergizing in the same 'feel', being friendly and helping each other to change. The change was caused by a modification to summarize the order of the wedding ceremony and a reduction in the number of participants or cultural actors involved, during the covid 19 pandemic. This has an impact on the degradation of the value of a Javanese wedding tradition. In the past, it was created by the ancestors to have hope as a symbol of the concept of prayer of hope, andum rasa (sharing happiness), guyub (crystallization of the value of harmony), tepa selira (understanding and respecting each other), tulung tinulung (helping each other), now everything is difficult to feel. People cannot be free to be part of the running of a tradition because of the prohibition on gathering and restrictions on community social activities. The results of this study are a scientific contribution and source of learning about socio-cultural changes in society and as a reference for stakeholder policies in taking strategic steps for implementing community activities during the COVID-19 pandemic.